Union Commitment: Is There a Gender Gap? - Wetzel, Kurt; Gallagher, Daniel; Soloshy, Donna (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
In the context of the growing feminization of membership in Canadian labour unions, this study examines the relationship between gender and multiple dimensions of worker commitment to the union organization. Based upon survey responses from 223 female and 222 male union members in Saskatchewan, the results reveal no gender differences with regard to expressed levels of union "loyalty" and "responsibility to the union". However, a small but significantly lower level of "willingness to work for the union" was expressed by female union members. In comparative analyses of males and females, the results are generally supportive of greater commonality than differences in the correlates of union commitment for men and women.